Producción musical del tema Going back to hometown de la banda Artificial Flavor - Fierro Conchambay, René Igor (2014)
This work shows the production process carried out to obtain the demo Going Back to Hometown of the band Artificial Flavor, an alternative rock and rock punk group from Quito whose proposal are very energetic songs in English. To start with the project, the objectives were set in order to periodically analyze their progress in relation to the available time. The predominant musical genre was researched and their influences were analyzed to determine the scope with the available materials, equipment, budget and locations. To facilitate the realization of this project it was divided into three stages, pre production, production and post production. In the pre production stage all the significant preparation points were defined in order continue with the following stages. The initial demo was analyzed and a new structure was given according to its genre and their musical references. The time and costs required for the implementation of the project were established and the art design was made to visually complement the sound work. During the production stage the recordings of all the elements of the song, battery, bass, guitars and voice were made. These sessions were accomplished applying the techniques learned during recording classes, and in different spaces available for its effect. Among them, they were the Universidad de las Americas recording studio, as well as also small home studios where technology was not necessarily the best and we had to draw on ingenuity and experimentation to solve problems that could appear. In the last stage the final shape and sonority was given to the recorded track during the production stage. To achieve this each of the instruments tracks were edited adapting them to a general level and time. These already edited tracks were mixed using positioning, frequency content and strength criteria to achieve a balance, space and complementation between instruments. Once mixed, the track was conditioned to achieve a standard level where it would reach its maximum sound potential with the best audio quality possible using EQ, compression and limiting, process known as mastering.